Universalizing health services in India: The techno-managerial fix - K R Nayar (Wolters Kluwer Medknow Publications, 2013)
The non-universal nature of health services in India can also be the result of many reforms and milestones the health services had passed through since independence. The reform era during the post-nineties is replete with many new trends in organizational strategies which could have led to crises in health services. The salient crises need to be dissected from a larger societal crisis and the specific crises in the health services system. It is evident that non-accessibility and non-availability and the sub-optimal functioning of the primary health centers are perennial issues which could not be addressed by indigenous, imposed or cocktail reforms (such as National Rural Health Mission) and by targeting as these only tinker with the health services. Needless to reiterate that there is a need to address the social dimensions which fall outside the technical sphere of health services. This paper based on an analytical review of relevant literature concludes that any efforts to universalize health and health-care can not only focus on technical components but need to address the larger social determinants and especially the societal crisis, which engender ill-health.